Axonal protein synthesis and the regulation of primary afferent function. Issue 3 (8th November 2013) - Obara, Ilona; Hunt, Stephen P.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Local protein synthesis has been demonstrated in the peripheral processes of sensory primary afferents and is thought to contribute to the maintenance of the neuron, to neuronal plasticity following injury and also to regeneration of the axon after damage to the nerve. The mammalian target of rapamycin (mTOR), a master regulator of protein synthesis, integrates a variety of cues that regulate cellular homeostasis and is thought to play a key role in coordinating the neuronal response to environmental challenges. Evidence suggests that activated mTOR is expressed by peripheral nerve fibers, principally by A‐nociceptors that rapidly signal noxious stimulation to the central nervous system, but also by a subset of fibers that respond to cold and itch. Inhibition of mTOR complex 1 (mTORC1) has shown that while the acute response to noxious stimulation is unaffected, more complex aspects of pain processing including the setting up and maintenance of chronic pain states can be disrupted suggesting a route for the generation of new drugs for the control of chronic pain. Given the role of mTORC1 in cellular homeostasis, it seems that systemic changes in the physiological state of the body such as occur during illness are likely to modulate the sensitivity of peripheral sensory afferents through mTORC1 signaling pathways. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 269–278, 2014